Electrochemistry at the interface between an aqueous droplet and 1,2-dichloroethane - Alam, M.; Sohail, M.; De Marco, Roland (Elsevier Inc., 2012)
Ion transfer in the absence of a dissolved redox couple at the interface between a droplet of water and 1,2-dichloroethane on a Ag/AgCl disc electrode has been studied in this communication. Due to the hemispherical shape of the water droplet, both planar and radial diffusion are contributing to the egress of ions during anodic stripping, while the ingress of ions during cathodic accumulation occurs solely via a planar diffusion mechanism, which was confirmed by changing the scan rates, volume of droplet and electrolyte.